European distribution and intramuscular pathogenicity of divergent lyssaviruses West Caucasian bat virus and Lleida bat lyssavirus - Stefania Leopardi; Laurent Dacheux; Jordi Serra-Cobo; Ágota Ábrahám; Branka Bajić; Hervé Bourhy; Szilárd-Lehel Bücs; Ivana Budinski; Martina Castellan; Petra Drzewniokova; Heliana Dundarova; Francesca Festa; et al. (iScience)
Summary: Among lyssaviruses, West Caucasian bat virus (WCBV) and Lleida bat lyssavirus (LLEBV) raise concern as their divergence from rabies virus leads to the inefficacy of available prophylactic agents. Both viruses were described in the bat Miniopterus schreibersii. We investigated the European distribution of WCBV and LLEBV by screening sera from Miniopterus schreibersii across eight countries, finding widespread serological evidence and positivity up to 70%. We evaluated the intramuscular lethality of wild type isolates in Syrian hamsters. WCBV induced 100% lethality and a clinical disease compatible with furious rabies. All animals infected with LLEBV remained healthy for 40 days, despite one individual testing positive in the brain. We confirmed LLEBV’s intramuscular a-pathogenicity using mice. Infected hamsters developed antibodies by day seven, regardless the virus and the clinical outcome. This study highlights the widespread circulation of WCBV and LLEBV in Europe and suggests differences in neuro-invasiveness and/or pathogenesis that are crucial for risk assessment.